Diversity and Inclusion in the Workplace: Assessing Their Effects on Employee Performance and Innovation - Suparyanto, Tri; santosa, Tomi Apra; Fauzi, Rizal Ula Ananta; Nungraha, Aat Ruchiat; Dewanto, Dewanto; Tarmizi, Rasyid (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to explore the impact of diversity and inclusion in the workplace on employee performance and innovation in organisations. In the context of increasing globalisation, companies are faced with the challenge of creating an inclusive work environment, where different cultural backgrounds, genders, and experiences can contribute to the maximum. This research methodology uses a quantitative approach with a survey involving 20 respondents from various industrial sectors. The data was analysed using multiple regression techniques to identify the relationship between diversity, inclusion, employee performance, and level of innovation. The results showed that there is a significant positive relationship between team diversity and improved individual performance as well as collaboration between team members. In addition, an inclusive work environment was shown to encourage creativity and new product innovation. The research also found that companies that actively implement diversity policies experience increased job satisfaction among their employees.